Porcelain fused to metal in vital crown with extensive caries at dentin depth: A case report: Porcelain fused to metal pada mahkota vital dengan karies luas pada kedalaman dentin: Laporan kasus - Rizka Rachmatika Dewi; Bambang Tri Hartomo; Fadli Ashar (Makassar Dental Journal PDGI Makassar, 2021)
Background: Anterior teeth are closely related to appearance and aesthetics. Extensive caries and reaching the depth of dentin reduce the aesthetic value so it needs to be treated with an artificial crown because it takes incisal load when used for cutting food, and aesthetics. The use of porcelain fused to metal is based on the strength and aesthetic properties of the material. Ob-jective: To determine the procedure for treating jacket crowns using PFM for teeth with caries reaching the dentin. Case: A 35-year-old man came to RSGM Unsoed wanting to treat his front upper right tooth with a large cavity. The patient feels pain when eats or drinks cold food and drinks. Management: Making artificial crown using PFM for strength and good aesthetics. Conclusion: The PFM is the restoration has good strength and aesthetics, so as to get maximum treatment results.